Glucose Deprivation Induces G2/M Transition-Arrest and Cell Death in N-GlcNAc(2)-Modified Protein-Producing Renal Carcinoma Cells - Isono, Takahiro (Public Library of Science, 2014)
Some cancer cells can survive under glucose deprivation within the microenvironment of a tumor. Recently, we reported that N-linked (β-N-acetylglucosamine)(2) [N-GlcNAc(2)]-modified proteins induce G2/M arrest and cell death under glucose deprivation. Here, we investigated whether such a response to glucose deprivation contributes to the survival of renal cell carcinomas, which are sensitive to nutritional stress. Specifically, we analyzed seven renal carcinoma cell lines. Four of these cell lines produced N-GlcNAc(2)-modified proteins and led G2/M-phase arrest under glucose deprivation, leading to cell death. The remaining three cell lines did not produce N-GlcNAc(2)-modified proteins and undergo G1/S-phase arrest under glucose deprivation, leading to survival. The four dead cell lines displayed significant up-regulation in the UDP-GlcNAc biosynthesis pathway as well as increased phosphorylation of p53, which was not observed in the surviving three cell lines. In addition, the four dead cell lines showed prolonged up-regulated expression of ATF3, which is related to unfolded protein response (UPR), while the surviving three cell lines showed only transient up-regulation of ATF3. In this study, we demonstrated that the renal carcinoma cells which accumulate N-GlcNAc(2)-modified proteins under glucose deprivation do not survive with abnormaly prolonged UPR pathway. By contrast, renal carcinoma cells that do not accumulate N-GlcNAc(2)-modified proteins under these conditions survive. Morover, we demonstrated that buformin, a UPR inhibitor, efficiently reduced cell survival under conditions of glucose deprivation for both sensitive and resistant phenotypes. Further studies to clarify these findings will lead to the development of novel chemotherapeutic treatments for renal cancer.